Clinical diagnostic significance of prealbumin, cholinesterase and retinol binding protein in liver cirrhosis combined with encephalopathy. Issue 1 (2nd January 2019) - Tan, L; Meng, Y; Zeng, T; Wang, Q; Long, T; Wu, S; Guan, X; Fu, H; Zheng, W; Tian, Y; Chen, J; Yu, J; et al.
ABSTRACT: Objective : Hepatic encephalopathy is a common consequence of liver cirrhosis, but diagnosis can be difficult as it is based on clinical criteria alone. We hypothesised that serum prealbumin, cholinesterase and retinol binding protein (RBP) can help support the diagnosis of hepatic encephalopathy. Methods : We enrolled 306 cirrhotic patients (110 with encephalopathy), 100 chronic hepatitis B patients and 50 healthy controls, measuring routine liver function tests (ALT, AST, GGT, ALP, and bilirubin), albumin, prothrombin time, prealbumin, cholinesterase and RBP by routine methods. Logistic regression analysis and areas under the receiver operating characteristic curves (AUCs) were used to find predictive factors for hepatic encephalopathy. Results : There were differences in all laboratory indices between the three groups (all p < 0.001). In univariate analysis, albumin, prothrombin time, prealbumin, cholinesterase and RBP were significantly altered in those with encephalopathy ( p < 0.01), but only prealbumin, cholinesterase and RBP levels were significant predictors in multivariate analysis, and each was linked to the severity of liver fibrosis defined by the Child-Pugh score (all p < 0.001). The AUCs (95% CI) of prealbumin, cholinesterase and RBP for diagnosing liver cirrhosis with hepatic encephalopathy were comparable at 0.85 (81–90), 0.81 (0.76–0.85) and 0.81 (0.76–0.86), respectively (all p < 0.01). Conclusions : Serum prealbumin, cholinesterase and RBP levels are of potential clinical value in diagnosis of liver cirrhosis complicated by encephalopathy.